(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Radiation therapy of skin cancer using beta particles can be an interesting treatment when the lesion is very superficial. Due to their low penetration depth in tissue, beta particles can well protect underlying sensitive structures such as bone. 3D printing technology can be used to create applicators, for beta-emitters, that are made based on the individual shape and size of the tumor. The tumor-volume optimized applicator limits and shapes the beta radiation dose to the tumor surface anatomy while protecting healthy tissue nearby. This study illustrates the workflow to fabricate these tumor-specific applicators.